Tracing pottery-making recipes in the prehistoric Balkans 6th-4th millennia BC - Amicone, Silvia; Quinn, Patrick S.; Marić, Miroslav; Mirković-Marić, Neda; Radivojević, Miljana (Archaeopress archaeology., 2019)
This is a collection of 12 chapters that capture the variety of current archaeological, ethnographic, experimental and scientific studies on Balkan prehistoric ceramic production, distribution and use. The Balkans is a culturally rich area at the present day as it was in the past. Pottery and other ceramics represent an ideal tool with which to examine this diversity and interpret its human and environmental origins. Consequently, Balkan ceramic studies is an emerging field within archaeology that serves as a testing ground for theories on topics such as technological know-how, innovation, craft tradition, cultural transmission, interaction, trade and exchange. This book brings together diverse studies by leading researchers and upcoming scholars on material from numerous Balkan countries and chronological periods that tackle these and other topics.